TRANSLATION-FACTORABLE SURFACES WITH VANISHING CURVATURES IN GALILEAN 3-SPACE - Kelleci, Alev (Bayram Sahin, 2021)
In this paper, we define two types of Translation-Factorable (TF-) surfaces in the Galilean 3-space. Then, we obtain the complete classification of these surfaces with vanishing Gaussian curvature and mean curvature and also, we give some explicit graphics of these surfaces. © 2021, Bayram Sahin. All rights reserved.
Keywords: factorable surfaces; Flat surfaces; Galilean space; minimal surfaces; translation surface